Development of upper body power in junior cross-country skiers - Nesser, T. W.; Chen, S.; Serfass, R. C.; Gaskill, S. E. (The Journal of Strength and Conditioning Research, 2004)
With the advent of the ski-skating technique, upper body power has increasingly been shown to be a major factor in cross-country skiing success. The purpose of this study was to evaluate 4 commonly used training methods (weight, circuit, rollerboard, and ski-specific training) for the development of upper body power (UBP) in junior cross-country skiers. Fifty-eight adolescent cross-country skiers (Boys: n = 29, age = 16.0 ± 1.2 y and Girls: n = 29, age = 15.5 ± 1.5 y) were assigned to one of the UBP training methods for a 10-week training program. Fourteen cross-country runners served as controls (boys: n = 7, age = 15.8 ± 1.7 y; girls: n = 7, age = 14.9 ± 1.3 y). Skiers were evaluated pre- and post-training for upper body strength (UBS) using a 10 repetition maximum (RM) rollerboard test, for UBP using a double-poling ergometer and for upper body endurance (UBE) with a 3-km, arms-only, rollerski endurance time trial. Competitive race results were collected during the winters before and after training as were all training data. Only the rollerboard training group improved significantly greater than the control group (p < 0.05) in UBP and UBS. Improvements in UBP, UPS, and UBE were significantly related (r = 0.545, 0.303, and 0.407, respectively) to improvements in competitive performance. These data suggest that training using a rollerboard with 5-12RM and explosive speed is more effective in developing UBP than other common training methods for adolescent cross-country skiers. The practical importance of these data was verified by the significant relationships between improvements in UBP, UBS, and UBE related to improvements in competitive race performance.